2022
DOI: 10.1186/s12884-022-04788-8
|View full text |Cite
|
Sign up to set email alerts
|

“Your heart keeps bleeding”: lived experiences of parents with a perinatal death in Northern Uganda

Abstract: Background Worldwide, two million babies are stillborn and 1.8 million babies die before completing seven days of life. Approximately 4% of pregnant women in Uganda experience perinatal death. The response following a perinatal death tends to be socio-culturally constructed. Investigating the unique personal experiences of parents from a low-income setting with unique cultural beliefs and practices is crucial for the design and implementation of appropriate interventions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…The lack of information, evasiveness, or misinformation from health professionals following stillbirth and fistula created anxiety in women and made them feel insignificant. These findings resonate with a previous study in Uganda, whereby healthcare providers were described as unsupportive following stillbirth, not providing consolation or an explanation about the cause of the stillbirth, with some mothers discovering the death themselves 19 . Similarly, a study of lived experiences in Malawi found women had little knowledge and understanding of fistula, unless a family member was previously affected, which led to misunderstanding and misattribution of the cause as the caesarean section surgery, their husband's unfaithfulness or witchcraft 20 .…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The lack of information, evasiveness, or misinformation from health professionals following stillbirth and fistula created anxiety in women and made them feel insignificant. These findings resonate with a previous study in Uganda, whereby healthcare providers were described as unsupportive following stillbirth, not providing consolation or an explanation about the cause of the stillbirth, with some mothers discovering the death themselves 19 . Similarly, a study of lived experiences in Malawi found women had little knowledge and understanding of fistula, unless a family member was previously affected, which led to misunderstanding and misattribution of the cause as the caesarean section surgery, their husband's unfaithfulness or witchcraft 20 .…”
Section: Discussionsupporting
confidence: 87%
“…Women did not expect poor outcomes and had to adjust and cope after their ‘dreams had been shattered’. Similarly, in Uganda, parents described the pain and confusion associated with stillbirth, feeling heartbroken returning home without their baby, and of coping with the loss of future dreams of the child growing up and supporting the family 19 . Women initiated coping mechanisms to conceal the loss or leakage associated with fistula, isolating away from other people or relocating to a new place, like what women described in Malawi 28 .…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations